Hands-On Systems Programming with Rust - Stocks, Nathan (Packt Publishing, 2020)
Take advantage of Rust to ensure safety and concurrency About This Video Quickly learn the essentials of systems programming in Rust and learn to monitor data flows through a pipeline Dive into a fast-paced and informative course which includes hands-on implementations of important concepts in every section Work with the latest version of Rust and develop a utility that's compatible with Linux, MacOS, and Windows In Detail Scripting languages will provide safety, but not concurrency and speed, while traditional systems programming languages such as C and C++ will definitely give you speed and some concurrency, but forget about safety! If you need safety, concurrency, and speed, then Rust is the only viable option. In this course, you will learn how Rust guarantees memory and thread safety at compile-time, yet uses zero-cost abstractions without the runtime overhead of a garbage collector. You'll learn how to monitor the flow of data through a pipeline by building your own middleware utility. You'll learn how to utilize I/O to interact with the command line, work with standard library mpsc channels to perform data flows, and create an ergonomic timer for your project. You'll apply key concepts in every section while creating your own middleware tool in Rust along the way. By the end of this practical course, you will feel comfortable designing safe, consistent, parallel, and high-performance applications in Rust using systems programming. This course should appeal to intermediate Linux and general Unix programmers, network programmers, and C/C++ programmers interested in learning different approaches to concurrency. Prior knowledge of basic programming concepts is required, and a working knowledge of Rust is assumed.